2015
DOI: 10.1103/physreve.92.062502
|View full text |Cite
|
Sign up to set email alerts
|

Light modulation in planar aligned short-pitch deformed-helix ferroelectric liquid crystals

Abstract: We study both experimentally and theoretically modulation of light in a planar aligned deformedhelix ferroelectric liquid crystal (DHFLC) cell with subwavelength helix pitch, which is also known as a short-pitch DHFLC. In our experiments, azimuthal angle of the in-plane optical axis and electrically controlled parts of the principal in-plane refractive indices were measured as a function of voltage applied across the cell. Theoretical results giving the effective optical tensor of a shortpitch DHFLC expressed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 53 publications
1
43
0
3
Order By: Relevance
“…The FLC-587-F7 is an eutectic mixture of the three compounds. The phase transition sequence of this FLC during heating from the preliminary obtained solid crystalline phase is: Cr  High-quality planar alignment yielding a contrast ratio more than 100:1 in white light is achieved using 4,4-oxydianiline dianhydride (PMDA-ODA) as 20 nm thick aligning layers according to the technique, which has been described in details in [15,16]. The obtained alignment was inspected by observing of textures within the cell in a polarizing microscope POLAM-P-312.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FLC-587-F7 is an eutectic mixture of the three compounds. The phase transition sequence of this FLC during heating from the preliminary obtained solid crystalline phase is: Cr  High-quality planar alignment yielding a contrast ratio more than 100:1 in white light is achieved using 4,4-oxydianiline dianhydride (PMDA-ODA) as 20 nm thick aligning layers according to the technique, which has been described in details in [15,16]. The obtained alignment was inspected by observing of textures within the cell in a polarizing microscope POLAM-P-312.…”
Section: Methodsmentioning
confidence: 99%
“…≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡ The above discussed effects of ellipticity modulation may affect the quality of the resulting light field formed by phase matrices. We estimated theoretically the possibility of formation of light fields with the required spatial parameters in such conditions, based on the calculation method described in [16,19], at  = 632.8 nm and D = 50 m. Special attention was paid to the formation of light fields in the form of specified curves possessing orbital angular momentum.…”
Section: жидк крист и их практич использ / Liq Cryst and Their mentioning
confidence: 99%
“…Such performance (response speed) restricts the possible scope of application for spatial light modulators (SLM) based on nematic LC. It is possible to increase in performance due to the orientation effects in ferroelectric liquid crystals (FLC) with sub-wavelength pitch of the spiral structure, in particular, orientational Kerr effect [1,2].Under this work the possibility of constructing spatial modulators of different types based on the cell with a ferroelectric liquid crystal with sub-wavelength pitch of the spiral and with the helicoid axis orientated along the substrates, is analyzed by the numerical simulation method.As soon as electric voltage is applied to the standard FLC cell with planar orientation of the main axis of the helix, then the change of the optical axis of the FLC layer direction and refractive indexes occurs. The change of the position of the optical axis of FLC in the plane perpendicular to the incident light wave direction causes the change in the state of polarization of the transmitted light.…”
mentioning
confidence: 99%
“…Such performance (response speed) restricts the possible scope of application for spatial light modulators (SLM) based on nematic LC. It is possible to increase in performance due to the orientation effects in ferroelectric liquid crystals (FLC) with sub-wavelength pitch of the spiral structure, in particular, orientational Kerr effect [1,2].…”
mentioning
confidence: 99%
“…In order to get around the optical axis switching problem the system based on the orientational Kerr effect in a vertically aligned deformed helix ferroelectric LC (DHFLC) with subwavelength helix pitch was suggested in [1,2]. In the geometry of a uniform lying helix, phase modulation of light in DHFLC cells was also studied using the experimental technique based on a Mach-Zehnder two-arm interferometer [3].In our recent paper [4], we have found that, for unpolarized incident light, the electro-optic response is insensitive to the effect of electric-field-induced rotation of in-plane optical axes and can be described in terms of the electrically dependent Pancharatnam phase. In this paper, we examine the electro-optic behavior of the planar aligned DHFLC cells illuminated with partially polarized light and extend our theoretical analysis of the Pancharatnam and geometric phases to the general case of mixed polarization states that undergo nonunitary and non-cyclic evolution.…”
mentioning
confidence: 99%